Conventional dipsticks in the screening of microalbuminuria and urinary tract infections. Killing 2 birds with one stone? - Rapi, Stefano; Bartolini, Laura; Puliti, Donella; Cambi, Giulia E.; Bamoshmoosh, Mohamed; Baldereschi, Marzia; Massetti, Luciano; Modesti, Pietro Amedeo (Saudi Medical Journal, 2010)
This brief report discusses the use of conventional urine dipsticks in screening for microalbuminuria and urinary tract infections, considering whether a simple screening approach may address two clinical objectives.